Trophoblast inclusions in the human placenta: Identification, characterization, quantification, and interrelations of subtypes. (1st January 2021) - Kliman, Harvey J.; Firestein, Morgan R.; Hofmann, Katherine M.; Milano, Kristin M.; Holzer, Parker H.; Brink, Lucy T.; Odendaal, Hein J.; Fifer, William P.
Abstract: We sought to examine placentas enriched for trophoblast inclusions (TIs) in order to characterize, quantify, and examine the interrelations between subtypes of TIs to better understand their underlying biology. We examined a cohort of 600 placentas from deliveries between 20 0 and 43 0 weeks of gestation. Forty-five percent of the placentas had at least one TI in the two slides examined. Four percent of the placentas had 10 or more TIs and two placentas had more than 70 TIs. Four distinct TI subtypes were observed: inclusionoids (early forming inclusions), inclusions, calcified inclusions, and calcified bodies. We suggest this reflects a developmental trajectory of TI maturation, the timing of which might be useful when comparing TI expression to clinical outcomes. Graphical abstract: Image 1 Highlights: TIs are formed by abnormal invagination of the trophoblast bilayer. TIs represent dysmorphic placental development. TIs are easily identified, if they are looked for. TIs progress through four morphologic stages.